Strengthening Student Character through the Implementation of Differentiated IPAS Learning Based on the Merdeka Curriculum - Egok, Asep Sukenda; Sari, Ratna Wulan; Susilo, Agus; Nabila, Salsa (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the implementation of differentiated Natural and Social Sciences (IPAS) learning in the Merdeka Curriculum as a means of strengthening student character at Uswatun Hasanah Elementary School in Lubuklinggau. The focus of the study is on the extent to which differentiation strategies can foster values of responsibility, discipline, cooperation, and curiosity in students. The research uses a quantitative and qualitative descriptive approach. Data were collected through observation, interviews, documentation, and student character assessment questionnaires filled out after the learning process. The research subjects involved teachers and 52 fourth and fifth grade students. The questionnaire analysis results showed that 82% of students were in the excellent category in the responsibility indicator, 79% in the cooperation indicator, 75% in the discipline indicator, and 81% in the curiosity indicator. These findings were reinforced by observation results showing an increase in student active participation in group discussions and perseverance in completing project-based assignments. Interviews with teachers also confirmed that differentiation of content, process, and product helped students learn according to their individual needs and learning styles. In conclusion, the implementation of differentiated IPAS learning in the Merdeka Curriculum has proven to be effective in strengthening the character of elementary school students, with questionnaire data showing positive improvements in almost all aspects of character. This study recommends that teachers continue to develop differentiation strategies as an integral part of character education in elementary schools.